2020
DOI: 10.1007/s40429-020-00316-w
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the Optimal Brain Target for Neuromodulation Therapies as Alcohol Addiction Progresses—Insights From Pre-Clinical Studies

Abstract: Purpose of the Review Development of addiction involves a transition from reward-driven to habitual behavior, mediated by neuroplastic changes. Based on preclinical findings, this article article reviews the current knowledge on the use of neuromodulation therapies to target alcohol addiction and essentially reduce relapse. Recent Findings To date, only a limited number of preclinical studies have investigated the use of neuromodulation in alcohol addiction, with the focus being on targeting the brain reward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 100 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Presently, several pre‐clinical studies are being performed using miRNAs as biomarkers or therapeutics for diseases, but no clinical trials, and few pre‐clinical trials, exist specifically for addiction (Creed, 2018; Dennis et al, 2020; Edemann‐Callesen, Barak, Hadar, & Winter, 2020; Whyte, Torregrossa, Barker, & Gourley, 2018). Many drug abuse studies rely on self‐reported data, and reliable diagnostics are difficult and expensive (Nora D. Volkow, Koob, & Baler, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, several pre‐clinical studies are being performed using miRNAs as biomarkers or therapeutics for diseases, but no clinical trials, and few pre‐clinical trials, exist specifically for addiction (Creed, 2018; Dennis et al, 2020; Edemann‐Callesen, Barak, Hadar, & Winter, 2020; Whyte, Torregrossa, Barker, & Gourley, 2018). Many drug abuse studies rely on self‐reported data, and reliable diagnostics are difficult and expensive (Nora D. Volkow, Koob, & Baler, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The mesocorticolimbic distribution of dopaminergic neurons is part of this pathway. The prefrontal cortex (PFC), amygdala (AMG), ventral tegmental area (VTA), and nucleus accumbens are the neuronal areas of the reward system [6], as shown in Figure 1.…”
mentioning
confidence: 99%